Comparing the Postoperative Outcomes of Single-Incision Laparoscopic Appendectomy and Three Port Appendectomy With Enhanced Recovery After Surgery Protocol for Acute Appendicitis: A Propensity Score Matching Analysis - Kim, Won Jong; Jin, Hyeong Yong; Lee, Hyojin; Bae, Jung Hoon; Koh, Wooree; Mun, Ji Yeon; Kim, Hee Ju; Lee, In Kyu; Lee, Yoon Suk; Lee, Chul Seung (Annals of coloproctology, 2021)
Purpose: The objective of this study was to compare the perioperative outcomes between single-incision laparoscopic appendectomy (SILA) and 3-port conventional laparoscopic appendectomy (CLA) in enhanced recovery after surgery (ERAS) protocol.Methods: Of 101 laparoscopic appendectomy with ERAS protocol cases for appendicitis from March 2019 to April 2020, 54 patients underwent SILA with multimodal analgesic approach (group 1) while 47 patients received CLA with multimodal analgesic approach (group 2). SILA and CLA were compared with the single institution’s ERAS protocol. To adjust for baseline differences and selection bias, operative outcomes and complications were compared after propensity score matching (PSM).Results: After 1:1 PSM, well-matched 35 patients in each group were evaluated. Postoperative hospital stays for patients in group 1 (1.2 ± 0.8 vs. 1.6 ± 0.8 days, P = 0.037) were significantly lesser than those for patients in group 2. However, opioid consumption (2.0 mg vs. 1.4 mg, P=0.1) and the postoperative scores of visual analogue scale for pain at 6 hours (2.4±1.9 vs. 2.8 ± 1.4, P = 0.260) and 12 hours (2.4 ± 2.0 vs. 2.9 ± 1.5, P = 0.257) did not show significant difference between the 2 groups.Conclusion: SILA resulted in shortening the length of hospitalization without increase in complications or readmission rates compared to CLA with ERAS protocol.